Glass powder, conductive paste containing glass powder, and crystalline silicon solar cell prepared from conductive paste

By using glass powder containing specific metal oxides to prepare conductive paste, the degradation problem caused by acetic acid corrosion of crystalline silicon solar cells is solved, and the effect of improving electrode tolerance and improving solar cell performance is achieved.

CN119707300APending Publication Date: 2025-03-28HERAEUS PHOTOVOLTAICS TECHNOLOGY (SHANGHAI) CO LTD

Patent Information

Application Number
CN202311230150.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-28

Smart Images

  • Figure CN119707300A_ABST
    Figure CN119707300A_ABST
Patent Text Reader

Abstract

The present invention relates to a glass frit comprising a base metal oxide and a specific metal oxide, the specific metal oxide being at 4 lt according to the Boubye diagram; pH lt; the total amount of the specific metal oxide is 0.1 to 10 mol%, preferably 1 to 5 mol%, and more preferably 2 to 4 mol%, based on the total amount of the metal oxide in the glass powder. The invention further relates to a conductive paste containing the glass powder, and a crystalline silicon solar cell prepared by using the conductive paste. Crystalline silicon solar cells of the present invention have reduced degradation due to acetic acid exposure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a glass frit, a conductive paste containing the glass frit, and a crystalline silicon solar cell prepared using the conductive paste. The cell has reduced degradation due to acetic acid exposure. Background Art

[0002] Crystalline silicon solar cells are devices that convert light energy from the sun into electrical energy. Light shines on a crystalline silicon wafer, generating electrons and holes, which are guided through electrodes located on the front side (i.e. the side illuminated by light) and the back side (i.e. the side not illuminated by light) of the substrate, thereby forming an electric current to obtain electrical energy.

[0003] The electrode on the side of the crystalline silicon wafer irradiated by light usually includes main grid lines and fine grid lines that are parallel to each other and perpendicular to each other. The main grid lines and fine grid lines are usually manufactured by applying a conductive paste on a substrate by screen printing and then sintering the conductive paste.

[0004] For example, CN110603648B and CN108806828B describe crystalline silicon solar cells, conductive pastes for preparing electrodes thereof, and preparation methods thereof.

[0005] The main and fine grid lines of crystalline silicon solar cells show degradation in long-term stability tests, resulting in reduced efficiency. It is generally believed that the above degradation is attributed to the corrosion of the interface area between the sintered glass and the grid lines by acetic acid produced by the ethylene-vinyl acetate polymer (EVA) used in photovoltaic modules when it comes into contact with water vapor.

[0006] For example, A. Kraft et al., “Investigation of Acetic Acid Corrosion Impact on Printed Solar Cell Contacts”, IEEE Journal of Photovoltaics, 5(3) pp. 736-743 discusses the mechanism of moisture-heat-induced degradation of screen-printed silver front electrodes of crystalline silicon solar cells in the presence of acetic acid and water vapor.

[0007] Therefore, there is a continuing need in the art to reduce the degradation of crystalline silicon solar cells due to acetic acid exposure. SUMMARY OF THE INVENTION

[0009] The applicant has found that by using glass powder containing specific metal oxides, preparing conductive paste therefrom, and further preparing solar cells, the corrosion resistance of the prepared electrodes to acetic acid corrosion can be significantly improved. The specific metal oxides are metal oxides that are not easily hydrolyzed in an environment of 4 < pH < 7 according to the Pourbaix diagram, such as oxides of metals selected from Be, Ce, Cr, Cu, Dy, Er, Fe, Ga, Ho, Nd, Nb, Pd, Pr, Sb, Tb, Ti, Yb, and Zr, preferably BeO, Ce 2 O 3 、Cr 2 O 3 、Cu 2 O, CuO, Dy 2 O 3 、Er 2 O 3 、Fe 2 O 3 、Ga 2 O 3 、Ho 2 O 3 、Nd 2 O 3 、Nb 2 O 5 、PdO, Pr 2 O 3 、Sb 2 O 3 、TbO 2 、TiO 2 、Yb 2 O 3 和ZrO 2 。

[0010] Preferably, the total amount of the above-mentioned specific metal oxides contained in the glass powder of the present invention is 0.1-10 mol%, preferably 1-5 mol%, more preferably 2-4 mol% based on the total amount of metal oxides in the glass powder.

[0011] Preferably, the glass powder of the present invention contains TiO 2 and / or Nb 2 O 5 , and optionally Ga 2 O 3 and optionally Sb 2 O 3 。

[0012] Compared with the existing glass powder, the crystalline silicon solar cell prepared from the glass powder of the present invention has improved Voc and improved corrosion resistance to acetic acid.

[0013] Specifically, the present invention includes the following:

[0014] The present invention relates to a glass powder, which comprises a base metal oxide and a specific metal oxide, and the specific metal oxide is a metal oxide that is not easily hydrolyzed in an environment where 4 < pH < 7 according to the Pourbaix diagram. Based on the total amount of metal oxides in the glass powder, the total amount of the specific metal oxide is 0.1 - 10 mol%, preferably 1 - 5 mol%, more preferably 2 - 4 mol%.

[0015] The specific metal oxide may be an oxide of a metal selected from Be, Ce, Cr, Cu, Dy, Er, Fe, Ga, Ho, Nd, Nb, Pd, Pr, Sb, Tb, Ti, Yb, and Zr, preferably selected from BeO, Ce 2 O 3 、Cr 2 O 3 、Cu 2 O, CuO, Dy 2 O 3 、Er 2 O 3 、Fe 2 O 3 、Ga 2 O 3 、Ho 2 O 3 、Nd 2 O 3 、Nb 2 O 5 、PdO, Pr 2 O 3 、Sb 2 O 3 、TbO 2 、TiO 2 、Yb 2 O 3 和ZrO 2 ;

[0016] The specific metal oxide may be an oxide of a metal selected from Ti, Nb, Ga, and Sb, preferably selected from TiO 2 、Nb 2 O 5 、Ga 2 O 3 和Sb 2 O 3 ;

[0017] The specific metal oxide may be TiO 2 和 / 或Nb 2 O 5 ,任选的Ga 2 O 3 ,以及任选的Sb 2 O3 ;

[0018] Based on the total amount of metal oxides in the glass powder, the glass powder may include:

[0019] 0.1-5 mol%, preferably 0.1-3 mol%, more preferably 0.2-2 mol% of Ti oxide, preferably TiO 2 ;

[0020] 0.1-6 mol%, preferably 0.1-4 mol%, more preferably 0.2-3 mol% of Nb oxide, preferably Nb 2 O 5 ;

[0021] 0-2 mol%, preferably 0-1.5 mol%, more preferably 0-1 mol% of Ga oxide, preferably Ga 2 O 3 ;

[0022] and

[0023] 0-3 mol%, preferably 0-2 mol%, more preferably 0-1.5 mol% of Sb oxide, preferably Sb 2 O 3 ;

[0024] The base metal oxide is one or more selected from oxides of metals Te, Pb, Si, Bi, B and Al, preferably selected from TeO 2 、PbO、SiO 2 、Bi 2 O 3 , B 2 O 3 、Al 2 O 3 One or more of, and:

[0025] Optional alkali metal oxide, preferably selected from Li 2 O、Na 2 O.K 2 O;

[0026] Optional alkaline earth metal oxides, preferably selected from MgO, CaO, SrO, BaO; and

[0027] Optional transition metal oxide, preferably selected from ZnO, Ag 2 O.WO 3 、MoO 3 , Mn 2 O 3 、MnO 2 ;

[0028] Based on the total amount of metal oxides in the glass powder, the glass powder may include:

[0029] 20-50 mol%, preferably 30-40 mol% TeO 2 ;

[0030] 10-30 mol%, preferably 15-25 mol% PbO;

[0031] 1-30 mol%, preferably 3-25 mol% SiO 2 ;

[0032] 3-15 mol%, preferably 5-10 mol% Bi 2 O 3 ;

[0033] 0-30 mol%, preferably 5-20 mol% of alkali metal oxides or combinations thereof;

[0034] 0-5 mol%, preferably 0.1-2 mol% of an alkaline earth metal oxide or a combination thereof; and

[0035] 0-40 mol%, preferably 5-25 mol% of transition metal oxides or combinations thereof;

[0036] The sum of the components of the glass powder is 100 mol%;

[0037] Wherein, based on the total amount of metal oxides in the glass powder, the glass powder may include:

[0038] 20-80 mol%, preferably 30-65 mol% of PbO and Bi 2 O 3 ;

[0039] 10-50 mol%, preferably 15-35 mol% SiO 2 and B 2 O 3 ;

[0040] 0-10 mol%, preferably 0-5 mol% Al 2 O 3 ;

[0041] 0-10 mol%, preferably 0-5 mol% of alkali metal oxides or combinations thereof;

[0042] 0-20 mol%, preferably 0-10 mol% of an alkaline earth metal oxide or a combination thereof; and 0-50 mol%, preferably 5-30 mol% of a transition metal oxide or a combination thereof;

[0043] The sum of the components of the glass powder is 100 mol%;

[0044] The glass powder may have a particle size D50 of 0.1-5 μm, preferably 0.2-4 μm, more preferably 0.4-3 μm;

[0045] After immersing 1 gram of the glass powder in 100 ml of 0.05 mol / L acetic acid solution and storing it at 90°C for two hours, the pH value of the acetic acid solution containing the glass powder at room temperature is less than 4, and the increase in the pH value of the acetic solution after the experiment can be 98% or less of the increase in the pH value of the acetic solution after the corresponding glass powder without the specific metal oxide is treated in the same way, preferably 95% or less, and more preferably 90% or less.

[0046] The present invention further relates to a conductive paste comprising silver powder, an organic vehicle and an optional conductive paste additive, and the above-mentioned glass powder;

[0047] The conductive paste may be a conductive silver paste, comprising silver powder, an organic carrier and an optional conductive paste additive, and the glass powder;

[0048] Based on the total amount of the conductive paste, the conductive paste may include

[0049] 1-10 wt. %, preferably 2-5 wt. % of glass powder, and

[0050] 60-95 wt %, preferably 85-90 wt % silver powder;

[0051] The sum of the components of the conductive paste is 100% by weight;

[0052] The conductive paste may be a conductive silver-aluminum paste, comprising silver powder, aluminum powder, silicon powder, an organic vehicle and an optional conductive paste additive, and the above-mentioned glass powder;

[0053] Based on the total amount of the conductive paste, the conductive paste may include

[0054] 1-15 wt. %, preferably 2-8 wt. % of glass powder, and

[0055] 50-95 wt %, preferably 80-90 wt % of silver powder, and

[0056] 0.1-5 wt. %, preferably 0.5-3 wt. % of aluminum powder, and

[0057] 0.01-5 wt %, preferably 0.05-3 wt % silicon powder;

[0058] The sum of the components of the conductive paste is 100 wt %.

[0059] The present invention further relates to a crystalline silicon solar cell comprising an electrode prepared from the above conductive paste;

[0060] The crystalline silicon solar cell may be a P-type solar cell, preferably a PERC solar cell, and its electrodes are obtained using a conductive paste containing the above glass powder or the above conductive paste;

[0061] The crystalline silicon solar cell may be an N-type solar cell, preferably a TOPCON solar cell, and its electrodes are obtained using a conductive paste containing the above glass powder or the above conductive paste.

[0062] The present invention further relates to a method for reducing the degradation of a crystalline silicon solar cell attributed to acetic acid exposure, wherein the electrodes of the crystalline silicon solar cell are obtained by applying a conductive paste containing a glass powder onto a silicon wafer and then sintering, and the glass powder contains a specific metal oxide which is a metal oxide that is not easily hydrolyzed in an environment with 4 < pH < 7 according to the Pourbaix diagram, and based on the total amount of metal oxides in the glass powder, the total amount of the specific metal oxide is 0.1-10 mol%, preferably 1-5 mol%, more preferably 2-4 mol%.

[0063] It is obvious to those skilled in the art that the above features can be combined arbitrarily. Description of the Drawings

[0064] Figure 1 is a schematic diagram of an apparatus for immersing a substrate with electrodes in acetic acid.

[0065] Figure 2 shows how to determine TiO from the Pourbaix diagram of the titanium-water system 2 which is a schematic diagram of a specific metal oxide used in the present invention.

[0066] Figure 3 shows how to determine Nb from the Pourbaix diagram of the niobium-water system 2 O 5 which is a schematic diagram of a specific metal oxide used in the present invention. Detailed Description of the Invention

[0067] Specific metal oxides

[0068] The applicant has found that by using a glass powder containing a specific metal oxide, preparing a conductive paste therefrom, and further preparing a solar cell, the crystalline silicon solar cell of the present invention can have an improved Voc and an improved tolerance to acetic acid corrosion.

[0069] The specific metal oxides of the present invention are metal oxides that are not easily hydrolyzed in an environment where 4 < pH < 7 according to the Pourbaix diagram, such as oxides of Be, Ce, Cr, Cu, Dy, Er, Fe, Ga, Ho, Nd, Nb, PdO, Pr, Sb, Tb, Ti, Yb, Zr, namely BeO, Ce 2 O 3 、Cr 2 O 3 、Cu 2 O, CuO, Dy 2 O 3 、Er 2 O 3 、Fe 2 O 3 、Ga 2 O 3 、Ho 2 O 3 、Nd 2 O 3 、Nb 2 O 5 、PdO、Pr 2 O 3 、Sb 2 O 3 、TbO 2 、TiO 2 、Yb 2 O 3 、ZrO 2 。

[0070] The Pourbaix diagrams of various metal and non-metal systems can be obtained from Atlas of Electrochemical Equilibria in Aqueous Solutions written by M. Pourbaix et al., published by Pergamon Press, Oxford, UK in 1966 and republished by the National Association of Corrosion Engineers, Texas, US in 1974.

[0071] For example, Figure 2 shows the Pourbaix diagram of the titanium-water system on page 217 of the second edition of Atlas of Electrochemical Equilibria in Aqueous Solutions at 25 °C, where Ti 2 O 3 and TiO 2 are anhydrous compounds.

[0072] Again, for example, Figure 3Shows the Pourbaix diagram of the niobium-water system at 25 °C on page 248 of the second edition of Atlas of Electrochemical Equilibria in Aqueous Solutions.

[0073] In the present invention, the meaning of "metal oxide that is not easily hydrolyzed in an environment where 4 < pH < 7 according to the Pourbaix diagram" is that on the Pourbaix diagram of the metal in the metal oxide, in the region enclosed by line (a) (i.e., the lower limit of the chemical stability of water), line (b) (i.e., the upper limit of the chemical stability of water), and the straight lines parallel to the Y-axis corresponding to pH values of 4 and 7, the stable state or equilibrium state of the system is the metal oxide or a compound in other non-dissolved ionic forms of the metal in the metal oxide.

[0074] For example, from Figure 2 it can be determined that TiO 2 belongs to the specific metal oxide used in the present invention. Specifically, Figure 2 is the Pourbaix diagram of the titanium-water system at 25 °C, which shows line (a) and line (b). Draw two straight lines parallel to the Y-axis corresponding to pH values of 4 and 7 on the diagram, thus obtaining the region enclosed by line (a), line (b), and the straight lines parallel to the Y-axis corresponding to pH values of 4 and 7. It can be seen from the diagram that in this region, the stable state is TiO 2 . Therefore, TiO 2 belongs to the specific metal oxide used in the present invention.

[0075] For another example, from Figure 3 it can be determined that Nb 2 O 5 belongs to the specific metal oxide used in the present invention. Specifically, Figure 3 is the Pourbaix diagram of the niobium-water system at 25 °C, which shows line (a) and line (b). Draw two straight lines parallel to the Y-axis corresponding to pH values of 4 and 7 on the diagram, thus obtaining the region enclosed by line (a), line (b), and the straight lines parallel to the Y-axis corresponding to pH values of 4 and 7. It can be seen from the diagram that in this region, the stable state is Nb 2 O 5 . Therefore, Nb 2 O 5 belongs to the specific metal oxide used in the present invention.

[0076] Glass powder

[0077] The first aspect of the present invention relates to a glass powder, which contains the specific metal oxide of the present invention and is used for preparing the conductive paste of the present invention.

[0078] In one embodiment of the present invention, the glass powder of the present invention comprises a specific metal oxide, wherein the total amount of the specific metal oxide is 0.1-10 mol %, preferably 1-5 mol %, based on the total amount of metal oxides in the glass powder.

[0079] In another embodiment of the present invention, the total amount of the specific metal oxide is 0.1-6 mol%, preferably 0.2-4 mol%, more preferably 0.5-1.5 mol%.

[0080] In one embodiment of the present invention, the glass powder of the present invention comprises the following specific metal oxides: TiO 2 and / or Nb 2 O 5 , optional Ga 2 O 3 , and optionally Sb 2 O 3 In other words, in this embodiment, the glass powder of the present invention comprises:

[0081] TiO 2 , optional Ga 2 O 3 , and optionally Sb 2 O 3 ;

[0082] Nb 2 O 5 , optional Ga 2 O 3 , and optionally Sb 2 O 3 ;or

[0083] TiO 2 and Nb 2 O 5 , optional Ga 2 O 3 , and optionally Sb 2 O 3 .

[0084] In a preferred embodiment of the present invention, the glass powder of the present invention comprises, based on the total amount of metal oxides in the glass powder:

[0085] 0.1-5 mol%, preferably 0.1-3 mol%, more preferably 0.2-2 mol% of Ti oxide, preferably TiO2;

[0086] 0.1-6 mol%, preferably 0.1-4 mol%, more preferably 0.2-3 mol% of Nb oxide, preferably Nb2O5;

[0087] 0-2 mol%, preferably 0-1.5 mol%, more preferably 0-1 mol% of Ga oxide, preferably Ga2O3; and

[0088] 0-3 mol%, preferably 0-2 mol%, more preferably 0-1.5 mol% of Sb oxide, preferably Sb 2 O 3 .

[0089] For example, the glass powder of the present invention may include:

[0090] 0.1 mol%, 0.2 mol%, 0.3 mol%, 0.4 mol%, 0.5 mol%, 0.6 mol%, 0.8 mol%, 1 mol%, 1.2 mol%, 1.4 mol%, 1.6 mol%, 1.8 mol%, 2 mol%, 2.5 mol%, 3 mol%, 3.5 mol%, 4 mol%, 4.5 mol% or 5 mol% of Ti oxide, preferably TiO 2 ;

[0091] 0.1 mol%, 0.2 mol%, 0.3 mol%, 0.4 mol%, 0.5 mol%, 0.6 mol%, 0.8 mol%, 1 mol%, 1.2 mol%, 1.4 mol%, 1.6 mol%, 1.8 mol%, 2 mol%, 2.5 mol%, 3 mol%, 3.5 mol%, 4 mol%, 4.5 mol%, 5 mol%, 5.5 mol% or 6 mol% of Nb oxide, preferably Nb 2 O 5 ;

[0092] 0.1mol%, 0.2mol%, 0.3mol%, 0.4mol%, 0.5mol%, 0.6mol%, 00mol%, 0.8mol%, 1mol%, 1.2mol%, 1.4mol%, 1.6mol%, 1.8mol% or 2mol% of Ga oxide, preferably Ga2O3;

[0093] 0 mol%, 0.8 mol%, 1 mol%, 1.2 mol%, 1.4 mol%, 1.6 mol%, 1.8 mol%, 2 mol%, 2.5 mol% or 3 mol% of Sb oxide, preferably Sb2O3.

[0094] In one embodiment of the present invention, the glass powder further comprises a base metal oxide, and the base metal oxide is one or more selected from oxides of metals Te, Pb, Si, Bi, B and Al, preferably selected from TeO 2 、PbO、SiO 2、Bi 2 O 3 , B 2 O 3 、Al 2 O 3 One or more of, and:

[0095] Optional alkali metal oxide, preferably selected from Li 2 O、Na 2 O.K 2 O;

[0096] Optional alkaline earth metal oxides, preferably selected from MgO, CaO, SrO, BaO; and

[0097] Optional transition metal oxide, preferably selected from ZnO, Ag 2 O, WO 3 、MoO 3 , Mn 2 O 3 、MnO 2 .

[0098] Specifically, in a particularly preferred embodiment of the present invention, as a glass powder for preparing a P-type solar cell, especially a PERC solar cell, based on the total amount of metal oxides in the glass powder, the glass powder of the present invention further comprises: 20-50 mol%, preferably 30-40 mol%, for example 30 mol%, 35 mol%, 40 mol% of TeO 2 ;

[0099] 10-30 mol%, preferably 15-25 mol%, for example 15 mol%, 20 mol%, 25 mol% PbO;

[0100] 1-30 mol%, preferably 3-25 mol%, for example 3 mol%, 5 mol%, 10 mol%, 15 mol%, 20 mol%, 25 mol% SiO 2 ;

[0101] 3-15 mol%, preferably 5-10 mol%, such as 5 mol%, 6 mol%, 8 mol%, 10 mol% Bi 2 O 3 ;

[0102] 0-30 mol%, preferably 5-20 mol%, for example 5 mol%, 10 mol%, 15 mol%, 20 mol% of alkali metal oxides or combinations thereof;

[0103] 0-5 mol%, preferably 0.1-2 mol%, such as 0.1 mol%, 0.5 mol%, 1 mol%, 1.5 mol%, 2 mol% of an alkaline earth metal oxide or a combination thereof; and

[0104] 0-40 mol%, preferably 5-25 mol%, for example 5 mol%, 10 mol%, 15 mol%, 20 mol%, 25 mol% of a transition metal oxide or a combination thereof;

[0105] The sum of the components of the glass powder is 100 mol%.

[0106] Specifically, in a particularly preferred embodiment of the present invention, as a glass powder for preparing an N-type solar cell, especially a TOPCON solar cell, based on the total amount of metal oxides in the glass powder, the glass powder of the present invention further comprises:

[0107] 20-80 mol%, preferably 30-65 mol% of PbO and Bi 2 O 3 ;

[0108] 10-50 mol%, preferably 15-35 mol% SiO 2 and B 2 O 3 ;

[0109] 0-10 mol%, preferably 0-5 mol% Al 2 O 3 ;

[0110] 0-10 mol%, preferably 0-5 mol% of alkali metal oxides or combinations thereof;

[0111] 0-20 mol%, preferably 0-10 mol% of an alkaline earth metal oxide or a combination thereof; and 0-50 mol%, preferably 5-30 mol% of a transition metal oxide or a combination thereof;

[0112] The sum of the components of the glass powder is 100 mol%.

[0113] It is known to those skilled in the art that in the above embodiments, PbO and Bi 2 O 3 and SiO 2 and B 2 O 3 The ratio is not critical.

[0114] The above-mentioned alkali metal oxides, alkaline earth metal oxides and transition metal oxides can be selected from the following metal oxides: Li 2 O、Na 2 O.K2 O, MgO, CaO, SrO, BaO, ZnO, Ag 2 O.WO 3 、MoO 3 , Mn 2 O 3 、MnO 2 .

[0115] In addition to the above-mentioned metal oxides, the glass powder according to the invention may also contain other compounds, in particular oxides, known to the person skilled in the art, which are usually added to glass powders, for example compounds, in particular oxides, of the following elements: P, V, Se, In, Sn, Ni, Ag, Ge, Tl, Sm and La.

[0116] In one embodiment of the present invention, the glass powder of the present invention can be prepared by the following method and then used to prepare the conductive paste of the present invention: all components of the glass powder are combined together to obtain a composition, the composition is melted to obtain glass, and quenched in deionized water, and finally the product is made into particles with a desired particle size to obtain the glass powder of the present invention.

[0117] Preferably, the “melting” is performed by charging the composition into a crucible, placing the crucible in a muffle furnace and melting the composition at a high temperature; the “water quenching” is performed by removing the molten glass from the muffle furnace and pouring it into a bucket filled with deionized water; and the “forming particles having a desired particle size” is performed by grinding the water-quenched glass slag with a ball mill to obtain glass powder having a desired particle size D50.

[0118] In the above method, the temperature of the muffle furnace is high enough to melt the components of the glass powder, and the melting time is long enough to uniformly mix the components.

[0119] More preferably, in the preparation of the glass powder, the temperature of the muffle furnace is 800-1500° C., preferably 900-1200° C., and the melting time of the mixture is 15 minutes to 2 hours, preferably 30 minutes to 1 hour.

[0120] Preferably, the glass powder of the present invention has a particle size D50 of 0.1-5 μm, preferably 0.2-4 μm, more preferably 0.4-3 μm. For example, the glass powder of the present invention can have a particle size D50 of 0.2 μm, 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm or 4.5 μm.

[0121] In another embodiment of the present invention, the glass powder of the present invention can be prepared by the following method and then used to prepare the conductive paste of the present invention: combining part of the components of the glass powder together to obtain a first composition, melting the first composition to obtain glass, quenching in deionized water, and finally making the product into first particles with a desired particle size; combining the remaining components of the glass powder together to obtain a second composition, melting the second composition to obtain glass, quenching in deionized water, and finally making the product into second particles with a desired particle size; combining the first particles and the second particles together to obtain the glass powder of the present invention.

[0122] The glass powder of the present invention can be divided into further parts and obtained by corresponding methods.

[0123] For example, in yet another embodiment of the present invention, the glass powder of the present invention can be prepared by the following method, and then used to prepare the conductive paste of the present invention: the first part of the components of the glass powder are combined together to obtain a first composition, the first composition is melted to obtain glass, and the product is quenched in deionized water, and finally the product is made into first particles with a desired particle size; the second part of the components of the glass powder are combined together to obtain a second composition, the second composition is melted to obtain glass, and the product is quenched in deionized water, and finally the product is made into second particles with a desired particle size; the remaining components of the glass powder are combined together to obtain a third composition, the third composition is melted to obtain glass, and the product is quenched in deionized water, and finally the product is made into third particles with a desired particle size; the first particles, the second particles, and the third particles are combined together to obtain the glass powder of the present invention.

[0124] Obviously, the above first particles, second particles and / or third particles etc. can be particles that have been prepared.

[0125] For example, in yet another embodiment of the present invention, the glass powder of the present invention can be prepared by the following method and then used to prepare the conductive paste of the present invention: combine part of the components of the glass powder together to obtain a first composition, melt the first composition to obtain glass, quench in deionized water, and finally make the product into first particles with a desired particle size; combine the first particles with second particles having the same composition as the combination of the remaining components of the glass powder to obtain the glass powder of the present invention.

[0126] Using already prepared particles as the above first particles, second particles and / or third particles, etc. may be advantageous because it provides a simple method for preparing the glass powder of the present invention.

[0127] The glass powder of the present invention has improved acid resistance, particularly acetic acid resistance, due to the inclusion of specific metal oxides.

[0128] For example, after treating the glass powder containing metal oxide in the form of immersion, the pH value of the acetic acid solution increases due to the reaction of acetic acid and the metal oxide. Accordingly, the acetic acid resistance of the glass powder can be evaluated by measuring the increase in the pH value of the acetic acid solution after treating the glass powder containing metal oxide. For example, the acetic acid resistance of the glass powder of the present invention can be evaluated using the following test method: 1 gram of the glass powder is immersed in 100 ml of 0.05 mol / L acetic acid solution and stored at 90° C. for two hours. The pH value of the acetic acid solution is measured at room temperature before and after immersion.

[0129] The pH value of the acetic acid solution after treating the glass powder of the present invention is less than 4 at room temperature.

[0130] The increase in pH of the acetic acid solution after treating the glass powder of the present invention is 98% or less, preferably 95% or less, and more preferably 90% or less, of the increase in pH of the acetic acid solution after treating the corresponding glass powder without the specific metal oxide of the present invention in the same manner.

[0131] Conductive paste

[0132] The second aspect of the present invention relates to a conductive paste, which is used to prepare the crystalline silicon solar cell of the present invention.

[0133] In one embodiment of the present invention, the conductive paste of the present invention comprises silver powder, the glass powder of the present invention, an organic vehicle and optional conductive paste additives.

[0134] In one embodiment of the present invention, the conductive paste of the present invention is a conductive silver paste.

[0135] Preferably, the conductive paste comprises silver powder which is commonly used in the art to prepare conductive paste for crystalline silicon solar cells.

[0136] Preferably, the particle size D50 of the silver powder may be 0.1-3 μm, preferably 0.1-1.5 μm or 0.1-2 μm.

[0137] Preferably, the conductive paste may contain 60-95 wt %, preferably 85-90 wt % of silver powder, based on the total weight of the conductive paste.

[0138] In another embodiment of the present invention, the conductive paste of the present invention is a conductive silver-aluminum paste.

[0139] Preferably, the conductive paste comprises silver powder, aluminum powder and silicon powder which are commonly used in the art to prepare conductive paste for crystalline silicon solar cells.

[0140] Preferably, the particle size D50 of the silver powder may be 0.1-5 μm, preferably 0.1-3 μm or 0.1-2 μm; the particle size D50 of the aluminum powder may be 0.1-10 μm, preferably 0.1-5 μm or 0.1-3 μm; the particle size D50 of the silicon powder may be 0.1-10 μm, preferably 0.1-5 μm or 0.1-3 μm.

[0141] Preferably, the conductive paste may contain 50-95 wt %, preferably 80-90 wt % silver powder, 0.1-5 wt %, preferably 0.5-3 wt % aluminum powder, 0.01-5 wt %, preferably 0.05-3 wt % silicon powder, based on the total weight of the conductive paste.

[0142] In one embodiment of the present invention, the conductive paste of the present invention comprises the glass frit of the present invention as described above.

[0143] In one embodiment of the present invention, the conductive paste of the present invention is a conductive silver paste, which contains 1-10 wt %, preferably 2-5 wt % of glass powder, based on the total weight of the conductive paste.

[0144] In one embodiment of the present invention, the conductive paste of the present invention is a conductive silver-aluminum paste, which contains 1-15 wt %, preferably 2-8 wt % of glass powder, based on the total weight of the conductive paste.

[0145] In one embodiment of the present invention, the conductive paste comprises an organic vehicle commonly used in the art, which is a solution, emulsion or dispersion based on one or more solvents, preferably an organic solvent, which ensures that the components of the conductive paste are present in a dissolved, emulsified or dispersed form. The preferred organic vehicle is an organic vehicle that provides the best stability of the components within the conductive paste and imparts viscosity to the conductive paste that allows effective printability.

[0146] In one embodiment, the amount of the organic vehicle may be 2-20 wt %, more preferably 3-15 wt %, and most preferably 5-10 wt %, based on the total weight of the conductive paste.

[0147] In one embodiment, the organic vehicle comprises an organic solvent, a binder (eg, a polymer, a resin), a surfactant, or an additive, or any combination thereof. For example, in one embodiment, the organic vehicle comprises one or more binders in an organic solvent.

[0148] The binder may be present in an amount of 0.1-10 wt %, preferably 0.1-8 wt %, more preferably 0.5-7 wt %, based on the total weight of the organic vehicle. Preferred binders are those that promote the formation of conductive pastes having favorable stability, printability, viscosity and sintering properties. Preferred binders (which generally fall within the category referred to as "resins") are polymeric binders, monomeric binders, and binders that are combinations of polymers and monomers. The polymeric binder may also be a copolymer.

[0149] Preferred polymeric binders include binders carrying functional groups in the polymer backbone, binders carrying functional groups outside the backbone, and binders carrying functional groups inside and outside the backbone. Preferred polymers carrying functional groups in the backbone include, for example, polyesters, substituted polyesters, polycarbonates, substituted polycarbonates, polymers carrying cyclic groups in the backbone, polysaccharides, substituted polysaccharides, polyurethanes, substituted polyurethanes, polyamides, substituted polyamides, phenolic resins, substituted phenolic resins, copolymers of one or more monomers of the above polymers (optionally with other comonomers) or combinations of at least two thereof.

[0150] Preferred polymers carrying cyclic groups in the main chain include, for example, polyvinyl butyral (PVB) and its derivatives and polyterpineol and its derivatives or mixtures thereof. Preferred polysaccharides include, for example, ethyl cellulose, cellulose and its alkyl derivatives, methyl cellulose, hydroxyethyl cellulose, propyl cellulose, hydroxypropyl cellulose, butyl cellulose, its derivatives and mixtures of at least two thereof. Other preferred polymers include, for example, cellulose ester resins, such as cellulose acetate propionate, cellulose acetate butyrate and any combination thereof. Other preferred polymers are those disclosed in U.S. Patent Application Publication No. 2013 / 0180583, which is incorporated herein by reference.

[0151] Preferred polymers carrying functional groups outside the polymer backbone are polymers carrying amide groups, polymers carrying acid and / or ester groups (commonly referred to as acrylic resins) or polymers carrying a combination of the above functional groups or combinations thereof. Preferred polymers carrying amide groups outside the backbone include, for example, polyvinyl pyrrolidone (PVP) and its derivatives. Preferred polymers carrying acid and / or ester groups outside the backbone include, for example, polyacrylic acid and its derivatives, polymethyl methacrylate (PMMA) and its derivatives or mixtures thereof.

[0152] Preferred monomeric binders include, for example, monomeric binders based on ethylene glycol. Preferred monomeric binders based on ethylene glycol are binders having multiple ether groups, multiple ester groups, or binders having one ether group and one ester group, and preferred ether groups are methyl, ethyl, propyl, butyl, pentyl, hexyl and higher alkyl ethers, and preferred ester groups are acetates and their alkyl ether derivatives, preferably ethylene glycol monobutyl ether monoacetate or mixtures thereof.

[0153] Preferred binders in the present invention are, for example, alkylcelluloses (preferably ethylcellulose), derivatives thereof and mixtures thereof with other binders from the previous list of binders.

[0154] The amount of the organic solvent may be 40 to 90% by weight, more preferably 35 to 85% by weight, based on the total weight of the organic vehicle.

[0155] Preferred solvents are solvents that allow the formation of an electroconductive paste having favorable viscosity, printability, stability and sintering properties. All solvents known in the art and considered suitable in the present invention can be used as solvents in the organic vehicle. According to the present invention, preferred solvents are solvents that allow the preferred high level of printability of the electroconductive paste as described above to be achieved. Preferred solvents according to the present invention are solvents that exist in liquid form at standard ambient temperature and pressure (SATP) (25°C, 100 kPa), preferably solvents having a boiling point above about 90°C and a melting point above about -20°C.

[0156] Preferred solvents are polar or nonpolar, protic or aprotic, aromatic or nonaromatic. Preferred solvents include, for example, monoalcohols, diols, polyols, monoesters, diesters, polyesters, monoethers, diethers, polyethers, solvents comprising at least one or more of these types of functional groups, optionally comprising other types of functional groups, preferably cyclic groups, aromatic groups, unsaturated bonds, alcohol groups having one or more O atoms substituted by heteroatoms, ether groups having one or more O atoms substituted by heteroatoms, ester groups having one or more O atoms substituted by heteroatoms, and mixtures of two or more of the above solvents.

[0157] The organic vehicle may also include a surfactant and / or an organic vehicle additive. The amount of the surfactant may be 0-10 wt %, preferably 0-8 wt %, more preferably about 0.01-6 wt %, based on the total weight of the organic vehicle. Preferred surfactants in the present invention are surfactants that promote the formation of conductive pastes with favorable stability, printability, viscosity and sintering properties. All surfactants known in the art and considered to be suitable in the present invention can be used as surfactants in the organic vehicle. Preferred surfactants may have nonionic, anionic, cationic, amphoteric or zwitterionic heads. Preferred surfactants are polymeric and monomeric or mixtures thereof.

[0158] Preferred organic vehicle additives in the organic vehicle are those that are different from the above-mentioned organic vehicle components and promote the favorable properties of the conductive paste (such as favorable viscosity and adhesion to the underlying substrate). Additives known in the art and considered suitable for use in the present invention can be used as organic vehicle additives. Preferred organic vehicle additives are thixotropic agents, viscosity regulators, stabilizers, inorganic additives, thickeners, emulsifiers, dispersants, slip agents or pH regulators and any combination thereof. Preferred thixotropic agents herein are carboxylic acid derivatives, preferably fatty acid derivatives or combinations thereof. Preferred fatty acid derivatives are C 9 H 19 COOH (decanoic acid), C 11 H 23 COOH (lauric acid), C 13 H 27 COOH (myristic acid), C 15 H 31 COOH (palmitic acid), C 17 H 35 COOH(stearic acid), C 18 H 34 O 2 (oleic acid), C 18 H 32 O 2 (linoleic acid) or a combination thereof. In this context, castor oil and hydrogenated castor oil are preferred.

[0159] In one embodiment of the present invention, the conductive paste optionally contains additives commonly used in the art. Preferred conductive paste additives are components added to the conductive paste in addition to the ingredients that have been explicitly mentioned, which are used to promote higher performance of the conductive paste, the electrode made therefrom, or the resulting crystalline silicon solar cell. All additives known in the art and considered applicable in the present invention can be used as conductive paste additives. Preferred conductive paste additives are thixotropic agents, viscosity regulators, emulsifiers, stabilizers or pH regulators, inorganic additives (such as silicon powder), thickeners and dispersants or a combination of at least two thereof, and inorganic additives are most preferred. Preferred inorganic additives are Mg, Ni, Te, W, Zn, Mg, Gd, Ce, Zr, Ti, Mn, Sn, Ru, Co, Fe, Cu and Cr or a combination of at least two thereof, preferably Zn, Sb, Mn, Ni, W, Te and Ru or a combination of at least two thereof, an oxide thereof, a compound that can produce the metal oxide upon firing, or a mixture of at least two of the above metals, a mixture of at least two of the above oxides, a mixture of at least two of the above compounds that can produce the metal oxide upon firing, or a mixture of two or more of any of the above materials. The amount of the inorganic additive may be 0-1 wt % (e.g., 0.1 wt %, 0.5 wt % or 0.8 wt %), based on the total weight of the conductive paste.

[0160] In one embodiment of the present invention, to form a conductive paste, the glass powder can be combined with silver powder, an organic vehicle, and optional conductive paste additives using any method known in the art for preparing a paste. The details of the preparation method are not critical, as long as it produces a homogeneously dispersed paste. The components can be mixed, such as with a mixer, and then passed through a three-roll mill, for example, to make a dispersed, uniform paste.

[0161] Crystalline silicon solar cells

[0162] The third aspect of the present invention relates to a crystalline silicon solar cell, which comprises a substrate and an electrode formed by sintering the conductive paste of the present invention and bonded to the substrate.

[0163] In one embodiment of the present invention, the preferred crystalline silicon solar cell according to the present invention is a crystalline silicon solar cell with high efficiency in terms of the ratio of the total energy of incident light converted into electrical energy output. Lightweight and durable crystalline silicon solar cells are also preferred. The crystalline silicon solar cell comprises at least: (i) a front electrode, (ii) a front doped layer, (iii) a pn junction boundary, (iv) a back doped layer and (v) a back electrode and (vi) a passivation layer. The crystalline silicon solar cell may also include additional layers for chemical / mechanical protection.

[0164] In one embodiment of the present invention, the crystalline silicon solar cell substrate of the present invention is a substrate for crystalline silicon solar cells known to those skilled in the art.

[0165] The crystalline silicon solar cell of the present invention basically comprises an electrode formed by sintering the conductive paste of the present invention and bonded to the substrate.

[0166] In one embodiment of the present invention, the conductive paste of the present invention is applied to a substrate, such as a semiconductor substrate (such as a crystalline silicon wafer), to form a printed electrode.

[0167] The conductive paste of the present invention can be applied to the substrate by any method known in the art and considered suitable in the present invention. Examples of such methods include, but are not limited to, dipping, impregnation, pouring, dripping, injection, spraying, blade coating, shower coating, brush coating or printing or a combination of at least two thereof. Preferably, the printing technique is inkjet printing, screen printing, flexographic printing, offset printing, relief printing or stencil printing or a combination of at least two thereof. It is preferred according to the present invention to apply the conductive paste of the present invention by printing, preferably by screen printing.

[0168] Firing is required to sinter the printed electrodes to form a solid conductor. Firing is well known in the art and may be achieved in any manner deemed appropriate in the present invention. It is preferred that firing is performed above the Tg of the glass frit material.

[0169] Outside the area occupied by the electrodes, the substrate of the present invention, preferably a crystalline silicon wafer, has an area where light can be efficiently absorbed to generate electron-hole pairs and efficiently separate holes and electrons across a boundary, preferably a pn junction boundary.

[0170] The pn junction boundary is located where the front doped layer of the wafer meets the back doped layer. In an n-type solar cell, the back doped layer is doped with an n-type dopant and the front doped layer is doped with a p-type dopant. In a p-type solar cell, the back doped layer is doped with a p-type dopant and the front doped layer is doped with an n-type dopant. According to a preferred embodiment of the present invention, a wafer having a pn junction boundary is prepared by first providing a doped silicon substrate and then applying a doped layer of the opposite type to one face of the substrate.

[0171] The above-mentioned dopants are preferably dopants that form pn junction boundaries by introducing electrons or holes into the band structure when added to the crystalline silicon wafer. According to the present invention, it is preferred to specifically select the types and concentrations of these dopants to adjust the band structure profile of the pn junction and set the light absorptivity and conductivity profile as required. The preferred p-type dopant according to the present invention is a dopant that adds holes to the band structure of the crystalline silicon wafer. All dopants known in the art and considered suitable in the present invention can be used as p-type dopants. The preferred p-type dopant according to the present invention is a trivalent element, especially a trivalent element of Group 13 in the periodic table. The preferred Group 13 elements in the periodic table herein include, but are not limited to, boron, aluminum, gallium, indium, thallium or a combination of at least two thereof, of which boron is particularly preferred.

[0172] Preferred n-type dopants according to the present invention are dopants that add electrons to the band structure of the crystalline silicon wafer. All dopants known in the art and considered suitable in the present invention can be used as n-type dopants. Preferred n-type dopants according to the present invention are elements of the fifth group of the periodic table. Preferred elements of the fifth group of the periodic table herein include nitrogen, phosphorus, arsenic, antimony, bismuth or a combination of at least two thereof, wherein phosphorus is particularly preferred.

[0173] In one embodiment of the present invention, according to the present invention, an antireflection layer may be applied as an outer layer before the electrode is applied to the front side of a crystalline silicon solar cell. A preferred antireflection layer according to the present invention is an antireflection layer that reduces the proportion of incident light reflected by the front side and increases the proportion of incident light that will be absorbed by the wafer across the front side. Antireflection layers that produce a favorable absorption ratio / reflection ratio are susceptible to etching by conductive pastes. In addition, antireflection layers that are resistant to the temperatures required for firing the conductive paste and do not promote greater recombination of electrons and holes near the electrode interface are preferred. All antireflection layers known in the art and considered suitable for use in the present invention can be used. A preferred antireflection layer according to the present invention is silicon nitride, silicon dioxide, aluminum oxide, titanium oxide, or a mixture of at least two thereof and / or a combination of at least two layers thereof. According to a preferred embodiment, the antireflection layer is silicon nitride, i.e., Si x N y , especially when crystalline silicon wafers are used, wherein x is about 2-4 and y is about 3-5.

[0174] In one embodiment of the present invention, one or more passivation layers may be applied to the substrate, preferably the front side and / or back side of the crystalline silicon wafer as an outer layer. The passivation layer may be applied before forming the front electrode or before applying the anti-reflection layer (if one of them exists). Preferably, the passivation layer is a passivation layer that reduces the electron / hole recombination rate near the electrode interface. Any passivation layer known in the art and considered applicable in the present invention may be used. According to the present invention, the passivation layer may be silicon nitride, aluminum oxide, silicon dioxide and titanium dioxide. According to the most preferred embodiment, aluminum oxide is used. Preferably, the passivation layer has a thickness of 0.1nm to 2μm, more preferably 1nm to 1μm, and most preferably 1nm to 200nm.

[0175] In one embodiment of the present invention, in addition to the above-mentioned layers which directly contribute to the main functions of the crystalline silicon solar cell, further layers may be added for mechanical and chemical protection.

[0176] The battery can be encapsulated to provide chemical protection. Encapsulation is well known in the art and any encapsulation suitable for the present invention can be used. According to a preferred embodiment, a transparent polymer (commonly referred to as a transparent thermoplastic resin) is used as an encapsulation material, provided that such an encapsulation exists. Preferred transparent polymers herein are silicone rubber and polyethylene vinyl acetate (EVA).

[0177] A transparent glass sheet may also be added to the front side of the crystalline silicon solar cell to provide mechanical protection thereto. Transparent glass sheets are well known in the art, and any transparent glass sheet suitable for use in the present invention may be employed.

[0178] A back protective material may be added to the back of the crystalline silicon solar cell to provide mechanical protection. Back protective materials are well known in the art and any back protective material deemed suitable in the present invention may be used. A preferred back protective material according to the present invention is a back protective material having good mechanical properties and weather resistance. A preferred back protective material according to the present invention is polyethylene terephthalate with a polyvinyl fluoride layer. It is preferred according to the present invention that the back protective material is present below the encapsulation layer (in the presence of a back protective layer and encapsulation).

[0179] Frame materials may be added to the outside of the crystalline silicon solar cell to impart mechanical support. Frame materials are well known in the art and any frame material deemed suitable for use in the present invention may be employed. A preferred frame structure according to the present invention is aluminum.

[0180] In a preferred embodiment of the present invention, the conductive paste of the present invention is used to prepare a P-type solar cell, in particular a PERC solar cell, and the conductive paste comprises the glass powder of the present invention, and the glass powder comprises:

[0181] 10-50 mol%, preferably 15-40 mol% TeO 2 ;

[0182] 10-30 mol%, preferably 15-25 mol% PbO;

[0183] 1-50 mol%, preferably 3-25 mol% SiO 2 ;

[0184] 3-15 mol%, preferably 5-10 mol% Bi 2 O 3 ;

[0185] 0-30 mol%, preferably 15-25 mol% of alkali metal oxides or combinations thereof;

[0186] 0-10 mol%, preferably 0.1-5 mol% of an alkaline earth metal oxide or a combination thereof; and

[0187] 0-40 mol%, preferably 5-25 mol% of transition metal oxides or combinations thereof.

[0188] In a preferred embodiment of the present invention, the conductive paste of the present invention is used to prepare an N-type solar cell, in particular a TOPCON solar cell, and the conductive paste comprises the glass powder of the present invention, and the glass powder comprises:

[0189] 20-80 mol%, preferably 30-65 mol% of PbO and Bi 2 O 3;

[0190] 10-50 mol%, preferably 20-35 mol% SiO 2 and B 2 O 3 ;

[0191] 0-20 mol%, preferably 0-10 mol% Al 2 O 3 ;

[0192] 0-20 mol%, preferably 0-10 mol% of alkali metal oxides or combinations thereof;

[0193] 0-30 mol %, preferably 0-15 mol % of an alkaline earth metal oxide or a combination thereof; and

[0194] 0-60 mol%, preferably 5-30 mol% of transition metal oxides or combinations thereof.

[0195] Example

[0196] The following examples show the glass powder of the present invention, the conductive paste comprising the glass powder of the present invention, and the crystalline silicon solar cell prepared from the conductive paste, and the preparation method and product performance thereof.

[0197] raw material

[0198] Al 2 O 3 , B 2 O 3 、Bi 2 O 3 , Ga 2 O 3 , Nb 2 O 5 , PbO, Sb 2 O 3 、SiO 2 、TeO 2 、TiO 2 , Li 2 O, CaO, and ZnO are 4N grade chemical reagents.

[0199] Silver powder, aluminum powder, and silicon powder are spherical powders with particle sizes D50 of 2 μm, 2 μm, and 1 μm, respectively.

[0200] P-type silicon wafer with silicon nitride passivation layer, size 182mm.

[0201] N-type silicon wafer with silicon nitride and aluminum oxide passivation layer, size 182mm.

[0202] The organic carrier is a mixture of solvent, resin, thixotropic agent and silicone oil, wherein the solvent is diethylene glycol butyl ether acetate, the resin is cellulose acetate butyrate, the thixotropic agent is hydrogenated castor oil, and the silicone oil is alkyl-modified silicone oil.

[0203] Acetic acid is an analytically pure chemical reagent.

[0204] The 0.05 mol / L acetic acid solution was obtained by diluting acetic acid with deionized water.

[0205] Preparation method of particles S1 to S14

[0206] Weigh the components of particles S1 to S14 according to the ratios shown in Table 1, respectively, and combine them together to obtain compositions corresponding to particles S1 to S14;

[0207] The obtained compositions were respectively loaded into alumina crucibles, placed in a muffle furnace and kept at 1100° C. for 60 minutes;

[0208] The alumina crucibles containing the molten glass were removed from the muffle furnace, and the molten glass was poured into a bucket containing deionized water for water quenching;

[0209] The water-quenched glass slag was respectively ground into a particle size D50 of about 1.5 μm using a ball mill, thereby obtaining particles S1 to S14.

[0210] Preparation method of glass powder

[0211] For the first and second groups of embodiments / comparative examples shown in Table 2, the first particles and the second particles of each embodiment are weighed according to the ratio shown in Table 2, and the particles are combined to obtain the glass powder of the embodiment / comparative example;

[0212] For example, Example 1 uses a glass powder obtained by combining 70 wt % of particles S14 and 30 wt % of particles S1;

[0213] For the third and fourth groups of embodiments / comparative examples shown in Table 2, the first particles shown in Table 2 are used as the glass powder of the embodiments / comparative examples respectively;

[0214] For example, Example 8 uses particles S8 as glass powder.

[0215] Method for preparing conductive paste

[0216] Silver powder, aluminum powder, silicon powder, glass powder and organic carrier were weighed respectively according to the ratio shown in Table 3, combined, mixed with a planetary mixer, and then mixed with a three-roll mill to prepare the conductive paste of each embodiment / comparative example.

[0217] Method for preparing substrate with electrode

[0218] The conductive paste of each embodiment / comparative example was respectively printed onto the silicon wafer of each embodiment / comparative example shown in Table 3 by screen printing, and then rapidly sintered under the conditions of a peak temperature of 750°C and a time of 16 seconds from room temperature to peak temperature to prepare a substrate with an electrode.

[0219] Test results of glass powder's acetic acid resistance

[0220] The acetic acid resistance of the glass powder is determined by the increase in the pH value of the acetic acid solution after the glass powder is treated in the form of immersion. The specific method is:

[0221] 1 gram of glass powder was immersed in 100 ml of 0.05 mol / L acetic acid solution and stored at 90°C for two hours. The pH value of the acetic acid solution was measured at room temperature before and after the immersion.

[0222] The acetic acid resistance test results of the glass powders of particles S13, S8, S14, S9, and S10 in Table 1 are the acetic acid resistance test results of the glass powders of Comparative Example 3, Example 8, Comparative Example 4, Example 9, and Example 10.

[0223] It was calculated that after the acetic acid tolerance test of Examples 8, 9, and 10 of the present invention containing specific metal oxides, the increase in the pH value of the acetic acid solution was 98.4%, 87.5%, and 75% of the increase in the pH value of the acetic acid solution after the acetic acid tolerance test of the corresponding Comparative Examples 3, 4, and 4 of the present invention treated in the same manner.

[0224] Battery performance measurement method

[0225] The acetic acid immersion experiment of the crystalline silicon wafer with electrodes was carried out by the following method:

[0226] Place the crystalline silicon wafers in a holder with a certain gap. Store the holder with the crystalline silicon wafers in a closed box together with a 3% acetic acid solution in an oven at 85°C for 18-20 hours to simulate the aging process of crystalline silicon solar cell modules in the presence of acetic acid vapor. Note that there is no direct contact between the silicon wafer and the acetic acid solution.

[0227] Before and after the acetic acid immersion test, the substrate with electrodes of each embodiment was subjected to IV test using a commercial IV tester "cetisPV-Celltest4-BF" from Halm Elektronik GmbH to obtain Eff (cell conversion efficiency), Voc (open circuit voltage), FF (fill factor), and calculate the decrease ratio of FF before and after the acetic acid immersion test. The results are shown in Table 4.

[0228] From the data in Table 4, we can see that after immersion in acetic acid, the 2 and / or Nb2 O 5 Examples 1-6, 7, 8, and 9-10 of the present invention achieve lower Eff drops than corresponding Comparative Examples 1, 2, 3, and 4, respectively, indicating reduced solar cell degradation due to acetic acid exposure. In particular, by using TiO 2 and Nb 2 O 5 Examples 2-5 and Example 7 respectively obtained lower Eff drops, indicating that the solar cell degradation attributed to acetic acid exposure was further reduced.

[0229] The data in Table 4 further show that before acetic acid immersion, the 2 and / or Nb 2 O 5 The Voc obtained in Examples 1-6, 7, 8 and 9-10 respectively did not change significantly compared with the corresponding Comparative Examples 1, 2, 3 and 4, which means that TiO 2 and Nb 2 O 5 The use of has no significant impact on the initial performance of solar cells.

[0230] The data in Table 4 further show that after immersion in acetic acid, the 2 and / or Nb 2 O 5 Examples 1-6, Example 7, Example 8 and Examples 9-10 respectively obtained higher Voc than the corresponding Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, which means that by using TiO 2 and / or Nb 2 O 5 , a solar cell with higher Voc after acetic acid exposure was obtained.

[0231]

[0232] Table 2: Composition of glass powder

[0233]

[0234] 2.1 Calculated based on the total amount of the first particle and the second particle

[0235] Table 3: Conductive paste composition and silicon wafer type

[0236]

[0237] 3.1 Calculated based on the total amount of glass powder

[0238] Table 4: IV test results before and after acetic acid immersion

[0239]

Claims

1. A glass powder, which comprises a base metal oxide and a specific metal oxide, wherein the specific metal oxide is a metal oxide that is not easily hydrolyzed in an environment with 4 < pH < 7 according to the Pourbaix diagram, and based on the total amount of metal oxides in the glass powder, the total amount of the specific metal oxide is 0.1-10 mol%, preferably 1-5 mol%, more preferably 2-4 mol%.

2. The glass powder of claim 1, wherein the specific metal oxide is at least one selected from the oxides of metals Be, Ce, Cr, Cu, Dy, Er, Fe, Ga, Ho, Nd, Nb, Pd, Pr, Sb, Tb, Ti, Yb, and Zr, preferably at least one selected from BeO, Ce2O3, Cr2O3, Cu2O, CuO, Dy2O3, Er2O3, Fe2O3, Ga2O3, Ho2O3, Nd2O3, Nb2O5, PdO, Pr2O3, Sb2O3, TbO2, TiO2, Yb2O3, and ZrO2.

3. The glass powder of claim 2, wherein the specific metal oxide is at least one selected from the oxides of metals Ti, Nb, Ga, and Sb, preferably at least one selected from TiO2, Nb2O5, Ga2O3, and Sb2O3.

4. The glass powder of claim 2, wherein based on the total amount of metal oxides in the glass powder, the specific metal oxide comprises: 0.1-5 mol%, preferably 0.1-3 mol%, more preferably 0.2-2 mol% of an oxide of Ti, preferably TiO2; 0.1-6 mol%, preferably 0.1-4 mol%, more preferably 0.2-3 mol% of an oxide of Nb, preferably Nb2O5; 0-2 mol%, preferably 0-1.5 mol%, more preferably 0-1 mol% of an oxide of Ga, preferably Ga2O3; and 0-3 mol%, preferably 0-2 mol%, more preferably 0-1.5 mol% of an oxide of Sb, preferably Sb2O3.

5. The glass powder of any one of claims 1-4, wherein the metal in the base metal oxide is one or more selected from Te, Pb, Si, Bi, B, and Al; and, optionally, an alkali metal oxide, wherein the alkali metal is at least one selected from Li, Na, and K; optionally, an alkaline earth metal oxide, wherein the alkaline earth metal is at least one selected from Mg, Ca, Sr, and Ba; and optionally, a transition metal oxide, wherein the transition metal is at least one selected from Zn, Ag, W, Mo, and Mn.

6. The glass powder of claim 5, wherein based on the total amount of metal oxides in the glass powder, the glass powder comprises: 20-50 mol%, preferably 30-40 mol% of TeO2; 10-30 mol%, preferably 15-25 mol% of PbO; 1-30 mol%, preferably 3-25 mol% of SiO2; 3-15 mol%, preferably 5-10 mol% of Bi2O3; 0-30 mol%, preferably 5-20 mol% of an alkali metal oxide or a combination thereof; 0-5 mol%, preferably 0.1-2 mol% of alkaline earth metal oxides or combinations thereof; and 0-40 mol%, preferably 5-25 mol% of transition metal oxides or combinations thereof; The sum of the components of the glass powder is 100 mol%.

7. The glass powder of claim 5, wherein the glass powder comprises, based on the total amount of metal oxides in the glass powder: 20-80 mol%, preferably 30-65 mol% of PbO and Bi2O3; 10-50 mol%, preferably 15-35 mol% SiO2 and B2O3; 0-10 mol%, preferably 0-5 mol% Al2O3; 0-10 mol%, preferably 0-5 mol% of alkali metal oxides or combinations thereof; 0-20 mol%, preferably 0-10 mol% of alkaline earth metal oxides or combinations thereof; and 0-50 mol %, preferably 5-30 mol % of a transition metal oxide or a combination thereof; The sum of the components of the glass powder is 100 mol%.

8. The glass powder according to any one of claims 1 to 7, having a particle size D50 of 0.1 to 5 μm, preferably 0.2 to 4 μm, more preferably 0.4 to 3 μm.

9. The glass powder according to any one of claims 1 to 7, characterized in that After immersing 1 gram of the glass powder in 100 ml of 0.05 mol / L acetic acid solution and storing it at 90°C for two hours, the pH value of the acetic acid solution containing the glass powder at room temperature is less than 4, and the increase in the pH value of the acetic solution after the experiment is 98% or less of the increase in the pH value of the acetic solution after the corresponding glass powder not containing the specific metal oxide is treated in the same way, preferably 95% or less, and more preferably 90% or less.

10. A conductive paste comprising silver powder, an organic vehicle and optionally a conductive paste additive, and the glass powder according to any one of claims 1 to 9.

11. The conductive paste of claim 10, which is a conductive silver paste, comprising silver powder, an organic vehicle and an optional conductive paste additive, and the glass powder of claim 6, based on the total amount of the conductive paste, the conductive paste comprises 1-10 wt. %, preferably 2-5 wt. % of glass powder, and 60-95 wt %, preferably 85-90 wt % silver powder; The sum of the components of the conductive paste is 100 wt %.

12. The conductive paste of claim 10, which is a conductive silver-aluminum paste, comprising silver powder, aluminum powder, silicon powder, an organic vehicle and an optional conductive paste additive, and the glass powder of claim 7, based on the total amount of the conductive paste, the conductive paste comprises 1-15 wt. %, preferably 2-8 wt. % of glass powder, and 50-95 wt %, preferably 80-90 wt % of silver powder, and 0.1-5 wt. %, preferably 0.5-3 wt. % of aluminum powder, and 0.01-5 wt %, preferably 0.05-3 wt % silicon powder; The sum of the components of the conductive paste is 100 wt %.

13. A crystalline silicon solar cell comprising an electrode prepared from the conductive paste according to any one of claims 10 to 12.

14. A method for reducing the degradation of crystalline silicon solar cells attributed to acetic acid exposure, wherein the electrodes of the crystalline silicon solar cells are obtained by applying a conductive paste containing a glass powder onto a silicon wafer and then sintering, and wherein the glass powder contains a base metal oxide and a specific metal oxide, the specific metal oxide being a metal oxide that is not easily hydrolyzed in an environment with 4 < pH < 7 according to the Pourbaix diagram, and wherein the total amount of the specific metal oxide is 0.1 - 10 mol%, preferably 1 - 5 mol%, more preferably 2 - 4 mol% based on the total amount of metal oxides in the glass powder.

Citation Information

Patent Citations

  • Conductive paste for solar cells, solar cells and their manufacturing methods, and solar cell modules

    CN108806828B

  • Conductive paste for the front side of crystalline silicon solar cells and its preparation method and solar cells

    CN110603648B

  • Conductive paste for fine-line high-aspect-ratio screen printing in the manufacture of semiconductor devices

    US20130180583A1

Cited By

  • High-nickel-content conductive paste for N-type Topcon photovoltaic cell and preparation method of high-nickel-content conductive paste

    CN121171686A

  • A high nickel content conductive paste for N-type topcon photovoltaic cells and a method of making the same

    CN121171686B